Moyamoya syndrome with antiphospholipid antibodies: a case report and literature review. (October 2014) - Wang, Z; Fu, Z; Wang, J; Cui, H; Zhang, Z; Zhang, B
Zhen Wang and Zhenqiang Fu contributed equally to this report. Moyamoya syndrome is a term applied to typical moyamoya vasculopathy with well-recognized associated conditions. Several systematic studies on the entities of moyamoya syndrome with autoimmune disease have been reported. We report a case of moyamoya syndrome with antiphospholipid antibodies and provide a review of relevant cases from the literature, describing the clinical characteristics and treatments.